Coupled fluid flow, heat transfer, phase transformation, stress and deformation numerical model for gas quenching. (21st May 2008) - Douce, J-F.; Bellot, J.P.; Denis, S.; Chaffotte, F.; Pellegrino, G.; Gouhinec, F.; Lamesle, P.; Maury, J.
Owing to the growing interest in high-pressure gas quenching, a complete mathematical modelling of this process has been launched with the aim of predicting the microstructural and mechanical state of steel bodies from the quenching operating conditions. The comprehensive numerical modelling combines the calculation of fluid flow and heat transport for the gaseous phase (using Fluent software) and calculation of heat conduction, solid-state phase transformations and residual stresses and distortions in the solid body (using Sysweld software). Our numerical results are compared to the experimental data obtained from a laboratory gas-quenching device set up at the Ecole des Mines d'Albi. Helium- and nitrogen-quenching trials were performed for nickel and 27MnCr5 steel cylinders. The measured gas flow velocities are compared to gas velocities calculated with the Fluent-Sysweld coupling, as well as the temperature evolutions at different locations in the cylinders. On the other hand, the ability of the model for predicting microstructure, residual stresses and deformations is illustrated with the gas quenching of a 60NiCrMo11 steel cylinder.